Design of a Birth Certificate Information System (Neonatal) Using the Waterfall Method at Santosa Hospital Bandung Kopo - Agustien, Rizty May; Abdussalaam, Falaah; Suryani, Ade Irma (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
A Birth Certificate is an essential document that confirms the birth of a child, issued by a hospital. This document is crucial for registering a child's birth and obtaining an official birth certificate. At Santosa Hospital Bandung Kopo, the process of creating Birth Certificates is currently done manually using Microsoft Excel, with data input based on handwritten forms filled out by the patient's family. This method is prone to data entry errors, leading to delays and inaccuracies in information. This study aims to design a Birth Certificate Information System that can improve the efficiency and accuracy of data processing. The system is developed using Microsoft Visual Studio 2010 with the Waterfall software development method. The research employs a qualitative method with a descriptive approach. Data was collected through interviews, observations, and literature reviews. The research instrument is a questionnaire consisting of five questions related to the process and challenges in creating Birth Certificates. The results of the study indicate that the designed system can minimize data entry errors and enhance the efficiency and accuracy in the creation of Birth Certificates at Santosa Hospital Bandung Kopo.